Long-Term Labeling of Hippocampal Neural Stem Cells by a Lentiviral Vector - Suh, Hoonkyo; Zhou, Qi-Gang; Fernandez-Carasa, Irene; Clemenson, Gregory Dane; Pons-Espinal, Meritxell; Ro, Eun Jeoung; Marti, Mercè; Raya, Angel; Gage, Fred H.; Consiglio, Antonella (Frontiers in Molecular Neuroscience, 2018)
Using a lentivirus-mediated tracing method, we investigated whether the adult hippocampus retains long-lasting, self-renewing neural stem cells (NSCs). We first showed that a single injection of a lentiviral vector expressing a green fluorescent protein (LV PGK-GFP) into the subgranular zone (SGZ) of the adult hippocampus enabled an efficient, robust, and long-term marking of self-renewing NSCs and their progeny. Interestingly, a subset of labeled cells showed the ability to proliferate multiple times and give rise to Sox2+ cells, clearly suggesting the ability of NSCs to self-renew for an extensive period of time (up to six months). In addition, using GFP+ cells isolated from the SGZ of mice that received a LV PGK-GFP injection three months earlier, we demonstrated that some GFP+ cells displayed the essential properties of NSCs, such as self-renewal and multipotency. Furthermore, we investigated the plasticity of NSCs in a perforant path transection, which has been shown to induce astrocyte formation in the molecular layer of the hippocampus. Our LV-mediated tracing study revealed that hippocampal NSCs are not responsible for the burst of astrocyte formation, suggesting that signals released from the injured perforant path did not influence NSC fate determination. Therefore, our studies showed that a gene delivery system using LVs is a unique method to be used for understanding the complex nature of NSCs and may have translational impact in gene therapy by efficiently targeting NSCs.